1990
DOI: 10.1007/bf01093455
|View full text |Cite
|
Sign up to set email alerts
|

Too hot for comfort: The heatwaves in Greece in 1987 and 1988

Abstract: The heatwaves that affected Greece in July 1987 and July 1988 are considered in terms of (i) the relative strain index. For different types of activity, and (ii) the discomfort index. Hourly values of air temperature and humidity for Thessaloniki and Athens were used as the data base. Both indices show that in terms of physiological strain and general discomfort, Thessaloniki suffered a little more and a little longer than Athens. We conclude that the relative strain index is probably a useful tool in studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
71
0
23

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(102 citation statements)
references
References 2 publications
0
71
0
23
Order By: Relevance
“…Outra equação foi proposta Giles et al (1990), utilizando umidade relativa em % em lugar da temperatura de bulbo úmido:…”
Section: A Escolha Do íNdiceunclassified
See 2 more Smart Citations
“…Outra equação foi proposta Giles et al (1990), utilizando umidade relativa em % em lugar da temperatura de bulbo úmido:…”
Section: A Escolha Do íNdiceunclassified
“…No entanto, a equação proposta por Giles et al (1990) com a umidade relativa também foi utilizada quando ocorreu ausência de dados de temperatura de bulbo úmido (em apenas 26 itens do cálculo). Thom (1959) expressa os resultados do índice com caráter adimensional (não acrescenta o símbolo ºF).…”
Section: A Escolha Do íNdiceunclassified
See 1 more Smart Citation
“…Several studies have examined thermal discomfort in Athens by applying a range of thermal comfort indices noting that, at times, levels of discomfort can be severe and occasionally last several days (e.g. see Metaxas, 1970;Giles et al, 1990;Matzarakis and Mayer, 1997;McGregor et al, 2002;Pantavou et al, 2008;Nastos and Matzarakis, 2012;Vouterakos et al, 2012). In a study which identified significant changes in the climatology of the season of thermal discomfort in Athens, McGregor et al (2002) suggested that a worthwhile line of research would be exploring the link between thermal discomfort and atmospheric circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Essa característica afeta diretamente o desempenho das atividades realizadas pelos indivíduos em seu interior e apresenta grande influência sobre a saúde humana. Donaisky et al (2010) afirmam que o conforto térmico tem efeitos diretos na produção e na satisfação de cada indivíduo.Condições climáticas urbanas inadequadas significam perda da qualidade de vida para uma parte da população, enquanto para outra, conduzem ao aporte de energia para o condicionamento térmico das edificações (ANDREASI et al, 2010;LAMBERTS et al, 1997). …”
unclassified